(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
The present article revised two sets of papers published during the second half of the twentieth century to show that fundamental behavior analysis principles were not abandoned and are still being used in clinical context, especially in Brazil. The first set is a review of B.F. Skinner’s main analysis referring clinical therapy; the second set describes both papers written by C.B. Fester about clinical proceeding. The topics deliberated by those authors are essential for practicing Behavior Analytic Therapy (TAC), with special importance for the Brazilian TAC. Some topics are relevant due to being a starting point for nowadays developments, while others still prevailing as clinical subjects of discussion. Also, a brief history of how TAC was described in other languages is presented, including its effect on Brazilian behavior analysis history. Revisiting this sets of papers allowed us to set out components that are still present in clinical practice, specially TAC, such as explaining client’s behavior in contingencies, teaching him to analyze its own behavior, methods of intervening during a clinical session, among others. It was possible to conclude that fundamental elements of Behavior Analysis are still present in clinical practice, particularly in Brazilian TAC.